Improving Listening Skills When Listening to Sentences and Conversations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article explores effective methods for developing listening and comprehension skills. It explains how to improve listening comprehension according to both the IELTS and CEFR frameworks. The article also highlights the importance of listening skills and emphasizes key aspects that learners should focus on during the listening process.